Efecto de productos Biofungicidas sobre la sanidad del cultivo de Arroz (Oryza sativa L.) en dos localidades de la Provincia de Los Ríos - Cano Maquilón, Jhon Luis (2022)
The present investigation was established on the grounds of the "Cacharí" Project and on the grounds of the Hda. La Esperanza, located in the Rcto. “La lucha”, Febres Cordero parish, Babahoyo Canton. SFL-11 rice seeds were used as planting material. In the trial, 10 treatments consisting of 2 locations and the biofungicides with their respective doses were used, such as: Bacillus subtilis (doses of 1.0 and 2.0 L/ha); Trichoderma sp. (doses of 2 and 3 g/kg); Bacillus subtilis + Trichoderma sp. (dose of 1.0 L/ha + 2.0 g/kg; 1.0 L/ha + 3.0 g/kg; 2.0 L/ha + 2.0 g/kg; 2.0 L/ ha + 3.0g/kg); Absolute control (dose 0) and chemical control (first application of Mancozeb + Cymoxanil at a dose of 1 kg/ha at 18 dat, the second application Difenoconazole + Propiconazole at a dose of 250 cc/ha at 38 dat and the third application Tebuconazole + Trifloxystrobin in doses of 600 cc/ha at 58 dat), with the experimental design called "Complete Blocks at Random" (DBCA), in factorial arrangement A x B, with two treatments, ten sub-treatments and three repetitions, applying the test Tukey's at the 0.05% level. According to the results obtained, it was determined that the highest incidence and illness of the diseases was observed in the control treatment, without the application of biofungicides, in both locations; the use of biofungicide products had a positive influence on the percentage of chlorophyll; the agronomic characteristics were influenced by the use of the products applied in rice cultivation and in the economic analysis a greater net benefit was obtained, with the application of Bacillus subtilis + Trichoderma sp. in doses of 2.0 L/ha + 2.0 g/kg.